Pengaruh Reward dan Punishment terhadap Motivasi Kerja Guru SMAN 1 Donggo Kabupaten Bima Cukup Signifikan - Farhan Pratama; Kristiana Sri Utami (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study was conducted on the teachers of SMAN 1 Donggo, Bima Regency, with the aim of identifying the impact of Reward and Punishment on work motivation. A quantitative research method was used with data analysis through the SPSS program. The study population consisted of teachers from SMAN 1 Donggo, with a sample of 50 respondents selected using a saturated sampling method. Data collection was carried out by distributing questionnaires online, with the research instrument using a Likert scale. Data analysis included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results showed that: first, based on the multiple linear regression analysis, the reward variable had a regression coefficient of 0.901, indicating that reward positively affects the improvement of work motivation. In contrast, the punishment variable had a regression coefficient of 0.174, showing that punishment negatively affects work motivation. Second, the F-test results showed that, together, reward (X1) and punishment (X2) had a significant effect on work motivation, with an F count of 48.407 greater than the F table value of 2.42 and a significance value of 0.000, which is less than 0.05. Third, reward (X1) significantly affected work motivation (Y), with a significance value of 0.000 less than 0.05 and a t-value of 9.342, which is greater than the t-table value of 1.677. Fourth, punishment (X2) also significantly affected work motivation (Y), with a significance value of 0.010 less than 0.05 and a t-value of 2.690, which is greater than the t-table value of 1.677. The results of this study indicate that reward has a greater impact on increasing work motivation, while punishment can reduce work motivation.